(untitled) (Research, Society and Development, 2020)
The present study sought to analyze how the interests of children and adolescents are regulated in the hypothesis of conjugal dissolution of their parents, especially with regard to custody, addressing the practical impracticality of shared custody, especially when the parents cannot even look at each other. In addition, the general and introductory concepts about the institute of custody were analyzed, as well as the principles of family law that influence, directly or indirectly, the attribution of custody. In addition, in methodological terms, the deductive method was used, starting from a general and abstract analysis of custody and the principles of family law, in order to arrive at a specific and concrete approach on the application of these precepts as a way to influence the attribution of unilateral custody, characterizing, therefore, some exceptions in which the predominance of shared custody is mitigated, in view of its practical impracticability. Finally, it was concluded that the observance of the Principle of the Best Interest of the Child leads the judge to decide, in certain cases, that unilateral custody should prevail over shared custody, considering that this does not always meet the interests of minors when faced with a marital dissolution, mainly because the parents, in most cases, have not obtained sufficient maturity to stop the fights and discussions about the relationship.